The Basics of Bacteriuria: Strategies of Microbes for Persistence in Urine - Ipe, Deepak S.; Horton, Ella; Ulett, Glen C. (Frontiers in Cellular and Infection Microbiology, 2016)
Bacteriuria, the presence of bacteria in urine, is associated with asymptomatic, as well as symptomatic, urinary tract infection (UTI). Bacteriuria underpins some of the dynamics of microbial colonization of the urinary tract, and probably impacts the progression and persistence of infection in some individuals. Recent molecular discoveries in vitro have elucidated how some key bacterial traits can enable organisms to survive and grow in human urine as a means of microbial fitness adaptation for UTI. Several microbial characteristics that confer bacteruric potential have been identified including de novo synthesis of guanine, relative resistance to D-serine, and catabolism of malic acid. Microbial characteristics such as these are increasingly being defined through the use of synthetic human urine (SHU) in vitro as a model to mimic the in vivo environment that bacteria encounter in the bladder. There is considerable variation in the SHU model systems that have been used to study bacteriuria to date, and this influences the utility of these models. In this review, we discuss recent advances in our understanding of bacteruric potential with a focus on the specific mechanisms underlying traits that promote the growth of bacteria in urine. We also review the application of SHU in research studies modeling UTI and discuss the chemical makeup, and benefits and limitations that are encountered in utilizing SHU to study bacterial growth in urine in vitro.